Stakeholder Perspectives of an Approach to Healthcare Leadership Development through Use of a Multidimensional Leadership Development Conceptual Model - Leigh, Jacqueline; Rutherford, June; Williamson, Tracey (International Journal of Practice-based Learning in Health and Social Care, 2017)
Leadership is often the driver used to transform healthcare services. Healthcare leadership development is often situated around conceptual frameworks or leadership development models. The aim of the study reported here was to evaluate multistakeholder perspectives on leadership development when applying a Multidimensional Leadership Development Conceptual Model to post-graduate healthcare leadership programmes at a university in England. This exploratory qualitative study of healthcare leadership development comprised face-to-face interviews. Six interviews were undertaken with academics from a post-graduate leadership programme team, a family carer and service-user of health care services, and current United Kingdom students and former United Kingdom and international students who had undertaken the leadership development programme. Transcripts were thematically analysed. Three themes emerged: Expectations of the contemporary healthcare leader; Experiences of the Multidimensional Leadership Development Conceptual Model on leadership development; and Improvements to the model. We conclude that framing post-graduate leadership programmes around a conceptual model can aid identification of the key components required for effective leadership development. Evidence-informed recommendations are provided which seek to optimise healthcare leadership development using a leadership development conceptual model which (1) represents the values and beliefs of all stakeholders involved; (2) is reviewed annually to critically explore the internal and external evidence base for leadership development; gain stakeholder consensus of expectations of the healthcare leader; and provide the reality check to ensure a ‘fit for purpose’ programme; and (3) is constructively aligned to leadership programme curricula with sufficient flexibility to tailor an effective teaching and learning platform for preparing the individual leader, noting unique circumstances and contexts.